Investigating the factors affecting the use of financial information in managerial decision-making in governmental organizations - Ghabdian, Mortaza; Ramezani, Yosef (International Review of Management and Marketing, 2018)
This study aims to investigate the factors affecting the usefulness of financial information in intra-organizational decision-making. The statistical population comprises all the auditors of the supreme audit court and the selected sample includes 118 auditors. This research is a descriptive-survey study and for data collection, questionnaire was used. The research findings with a structural equation modeling approach demonstrated that there is a significant positive relationship between the external and internal factors of the organization and usefulness of financial information in managerial decision-making. Also, findings revealed that of the organization's external factors, the role of the media and public networks has the greatest impact on the usefulness of financial information in intra-organizational decision-making and out of the organization's internal factors, the existence of sufficient computational tools has the greatest effect on the usefulness of financial information in intra-organizational decision-making. Besides, individual factors compared to organizational factors have more influence on the usefulness of financial information. Keywords: Usefulness of financial information, extra-organizational factors, intra-organizational factors, managerial decision-making, supreme audit court. JEL Classifications: G2, G41, L2